1973
DOI: 10.1159/000465608
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of a Dominant Inhibitor of the Lutheran Antigens

Abstract: A family is reported in which the phenotype Lu(a-b-) is present in three generations. The family shows that the inhibitor, known to be dominant in effect, which prevents the proper expression of Lu^b, prevents also that of Lu^a. It further shows that the inhibitor locus is not part of the Lutheran locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The inheritance of Vel has been usually considered to be due to a high-frequency dominant gene, Vea, and the Vel(-) phenotype to represent a rare recessive condition. However, RACE and SANGER [16] suggest that the existence of families with Vel(-) individuals in two and three successive generations [l, 111 and sibships with too many Vel(-) present [25] may indicate another mode of inheritance, and that in these families a dominant inhibitor gene, which may or may not be part of the Vel locus, could be responsible as has been found in the Lutheran system [23].…”
Section: Discussionmentioning
confidence: 99%
“…The inheritance of Vel has been usually considered to be due to a high-frequency dominant gene, Vea, and the Vel(-) phenotype to represent a rare recessive condition. However, RACE and SANGER [16] suggest that the existence of families with Vel(-) individuals in two and three successive generations [l, 111 and sibships with too many Vel(-) present [25] may indicate another mode of inheritance, and that in these families a dominant inhibitor gene, which may or may not be part of the Vel locus, could be responsible as has been found in the Lutheran system [23].…”
Section: Discussionmentioning
confidence: 99%
“…TALIANO et al [16] have suggested the name In(Lu) for the rare regulatory gene, at an independent locus, which inhibits expression of the Lutheran genes. If it is assumed that inheritance of the same modifying gene is the The pedigree in figure 1 has been compiled from family and church records.…”
Section: Serological Findingsmentioning
confidence: 99%
“…1974). The dominant background arises from the inheritance of an autosomal dominant suppressor gene In(Lu) (Taliano et al 1973) and the third background arises from the inheritance of a recessive X-borne suppressor gene Xi92 (Norman et al 1986). Some of the Lu(b-) donors identified by screening the South Wales blood donor population with anti-Lub to identify Lu(b-) donors for the rare donor registries were found to be Lu(a-b-).…”
Section: Introductionmentioning
confidence: 99%